1994
DOI: 10.3354/meps108001
|View full text |Cite
|
Sign up to set email alerts
|

Activity and distribution of attached bacteria in Chesapeake Bay

Abstract: The purpose of this study was to further our understanding of the role of particle-associated bacteria in phytoplankton degradation in the Chesapeake Bay, USA, and to identify environmental parameters that control production by free and particle-associated bacteria. Surface and bottom waters at 10 stations along the length of the Bay were sampled over a 2 yr period. Samples were analyzed for temperature, salinity, chlorophyll, phaeophytin, particulate protein, thymidine incorporation (an estimate of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 17 publications
3
36
1
Order By: Relevance
“…The increased C-transfer in to microbial biomass in our Protist treatment, where bacterial aggregation was more common, is consistent with evidence that bacteria in microcolonies or aggregates are more efficient in DOC-uptake and express a higher cell-specific production than free-living cells (Griffith et al 1994, Grossart et al 2003, 2007. This may reflect a general difference between diffusion-limitation of access to C-sources in free-living and aggregated cells (Guasto et al 2012).…”
Section: Discussionsupporting
confidence: 65%
“…The increased C-transfer in to microbial biomass in our Protist treatment, where bacterial aggregation was more common, is consistent with evidence that bacteria in microcolonies or aggregates are more efficient in DOC-uptake and express a higher cell-specific production than free-living cells (Griffith et al 1994, Grossart et al 2003, 2007. This may reflect a general difference between diffusion-limitation of access to C-sources in free-living and aggregated cells (Guasto et al 2012).…”
Section: Discussionsupporting
confidence: 65%
“…Nevertheless, through the low abundance of aggregates the number of attached bacteria represented only 0.1 to 4.4% of the total number of bacteria in the surface water of the North Atlantic. In Antarctic regions of the Atlantic Ocean about 20% of bacteria were associated with particles (Delille 1993), and in Chesapeake Bay less than 10% were found on particles (Griffith et al 1994). On the basis of high I4C-glucose uptake a.nd low Q-thymidine incorporation, Kirchman (1983) concluded that bacteria on particles have a high metabolism but a low frequency of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, specific (per cell) activities (growth rates and ectoenzymatic activities) of particle-attached bacteria were significantly higher than those of free-living bacteria. Other studies have shown that bacteria inhabiting marine snow have cell-specific ectoenzymatic activities up to 3 orders of magnitude higher than bacteria in the surrounding water (Karner & Herndl 1992, Smith et al 1992, Griffith et al 1994, Martinez et al 1996. Delong et al (1993) found that particle-attached bacteria were phylogenetically distinct from free-living bacteria and were able to degrade a wide range of polymeric compounds.…”
Section: Discussionmentioning
confidence: 99%